Interleukin-33/ Suppression of Tumorigenicity 2 in Renal Fibrosis: Emerging Roles in Prognosis and Treatment - Tan, Xiao-Yang; Jing, Hao-Yue; Ma, Yue-Rong (Frontiers in Physiology, 2022)
Chronic kidney disease (CKD) is a global public health problem and has a high mortality rate, affecting more than 10% of the population worldwide. Therefore, it is necessary to find out novel treatment strategies for CKD. Renal fibrosis plays a central role in the progression of CKD to end-stage renal disease. The activation of inflammatory pathways contributes to renal fibrosis. Being a new member of the interleukin 1 (IL-1) cytokine family, IL-33 is a crucial regulator of the inflammatory process. It exerts proinflammatory and profibrotic effects via the growth-stimulated expression gene 2 (ST2) receptor that activates other inflammatory pathways. The IL-33/ST2 pathway is involved in the development of renal fibrosis. Traditional Chinese medicine has a history of treating renal diseases for thousands of years.An increase in the utilization rate of traditional Chinese medicine is an important direction in carrying out research on renal fibrosis and developing novel treatment strategies for the treatment of renal fibrosis in the future.This review summarizes the role of the IL-33/ST2 pathway in renal fibrosis and the current scenario of herbal medicine research related to this pathway in order to explore possible future prospects for research on renal fibrosis and to identify potential targets for herbal medicine therapy.